Construction project safety - Schaufelberger, John, 1942-; Lin, Ken-Yu, 1975- (Wiley, 2014)
"This introduction to construction safety for construction management personnel takes a project-based approach to present potential hazards in construction and their mitigation or prevention. After introducing Accident Prevention Programs and OSHA compliance requirements, the book integrates safety instruction into the building process by following a building project from site construction through interior finish. Reinforcing this applied approach are photographs, drawings, contract documentation, and an online 3D BIM model to help visualize the onsite scenarios"--